Burnout in municipalities : examining demographic differences in burnout and job satisfaction among municipal employees in Iceland - Sara Lind Sigurðardóttir 1999-; Guðrún Harpa Jóhannsdóttir 1999-; Rebekka Rós Björgvinsdóttir 1998- (2022)
Burnout and job satisfaction are important concepts that, both individually and together, affect employee wellbeing. The aim of this study was to investigate burnout and job satisfaction with emphasis on their relationship with gender and age and explore whether there is a correlation between burnout and job satisfaction. Six research questions were put forth: (1) How prevalent is burnout among municipal employees in Iceland? (2) Are there differences in burnout between genders? (3) Are there differences in burnout between age groups? (4) Are there differences in job satisfaction between genders? (5) Are there differences in job satisfaction between age groups? (6) Is there a correlation between burnout and job satisfaction? An email containing the questionnaire was sent to 2192 individuals, and 1194 (54.5%) answered it altogether or partly. Just over 83% of participants were female, and the average age was 47 years old. Independent-samples t-test was used to examine uncategorized burnout symptoms by gender and determine if there were any gender differences. One-way ANOVA and the Bonferroni post hoc test were used to examine age differences in burnout and job satisfaction. Chi-square was used to examine categorized burnout symptoms by gender, and job satisfaction by gender. Spearman’s rho was used to see if there were any correlations between burnout and job satisfaction. About 23% reported medium or large amounts of overall burnout symptoms. Males average burnout symptoms were higher compared to females average burnout levels. After categorizing burnout symptoms in relation to quantity, the chi-square test showed that women displayed higher burnout symptoms compared to men. There was a significant difference between age groups in all categories of burnout. There was a positive correlation between job satisfaction and burnout, indicating that as burnout increases, job satisfaction increases, as well. There was not a significant difference in job satisfaction between genders. These results demonstrate that ...